Matrix effect of five kinds of meat on colloidal gold immunochromatographic assay for sulfamethazine detection. Issue 37 (20th August 2018) - Liu, Namei; Xing, Keyu; Wang, Chun; Zhang, Ganggang; Yuan, Meifang; Li, Danhong; Lai, Weihua; Peng, Juan
Abstract : A colloidal gold immunochromatographic assay (CG-ICA) was developed to detect sulfamethazine (SM2 ) residues in five kinds of meat: namely, chicken, pork, shrimp, beef, and fish. Abstract : A colloidal gold immunochromatographic assay (CG-ICA) was developed to detect sulfamethazine (SM2 ) residues in five kinds of meat: namely, chicken, pork, shrimp, beef, and fish. The limit of detection (LOD) of CG-ICA for SM2 detection was 0.104 ng mL −1 within 20 min. CG-ICA exhibited a wide linear range of 0.1 ng mL −1 to 96 ng mL −1 with a reliable correlation coefficient ( R 2 = 0.9938). The average recoveries of CG-ICA for SM2 detection in chicken, pork, shrimp, beef, and fish were 98.1% ± 4.6%, 86.1% ± 0.5%, 86.2% ± 4.9%, 71.7% ± 1.7%, and 79.2% ± 2.5%, respectively. The matrix effect of the five kinds of meat on CG-ICA was also assessed. The standard curves of the five matrices did not coincide with the standard curve of phosphate buffer saline, indicating that a matrix effect had occurred in CG-ICA for SM2 detection in the five matrices. The strongest matrix effect was elicited by beef, followed by fish, pork, and shrimp, whereas the weakest matrix effect was produced by chicken.